Māḥauliyātī masāʼil, qānūnī aur intiẓāmī ṣūratiḥāl, Pākistān ke tanāẓar meṉ : Nīpā Pishāvar ke sātveṉ māḥauliyātī intiẓāmāt ke shurakā-yi kors - Naqvi, Hasan Mehdi (Pishāvar : Pākistān Ikaiḍaimī barāʼe Dehī Taraqqī, 1994)
Legal and administrative study of environmental problems in Pakistan; a study course conducted by National Institute of Public Administration, Peshawar, Pakistan.
"PARD/RES/137"--Cover.
Mode of access: Internet.
In Urdu.
Keywords: Environmental law -- Pakistan; Environmental policy -- Pakistan